State transgression on electronic expression: is it for real?. (9th October 2017) - Ray, Argha; Kaushik, Anjali
Abstract : Purpose: Cyberspace is a virtual environment where instantaneous communications are initiated and consumed using computer networks without any natural or artificial boundaries. These communications are not only an exchange of information but also a catharsis on the socio-political environment of the real world. This explosion of electronic expression is often detrimental to the traditional secretive maneuvers of nation states and the exercise of its power. Unable to come to terms with the new reality nation states through legislative action or otherwise attempt to assert its sovereignty in the space that has no political and societal boundaries. This may lead to an encroachment on basic human rights that often have constitutional guarantees in the real world but may be violated in the online milieu. This paper aims to investigate this issue in detail and evaluate whether nation states are using cyber-security as a propaganda tool to transgress on electronic expression. Design/methodology/approach: The Website of the UN Office of the High Commissioner for Human Rights states "In December 2013, the United Nations General Assembly adopted resolution 68/167, which expresses deep concern at the negative impact that surveillance and interception of communications may have on human rights". It further says "The General Assembly called on all States to review their procedures, practices and legislation related to communications surveillance, interception and collection of personal data and emphasized the need for States to ensure the full and effective implementation of their obligations under international human rights law". With this development, this paper seeks to unravel the role of nation states in using cybersecurity as a propaganda tool by raising the specter of threat to national security and economic wellbeing. The paper is based on exploratory research with data compilation from secondary sources. To collect data, various research papers, books and journals have been referenced and data available in public domain has been accumulated. Findings: This paper has tried to unravel state action on cyberspace which often runs counter to the concept of civil liberties. It indicates that in terms of both national security and economic impact, cybercrime represent a very nominal threat vector. Also, cybercrime as compared with other forms of crime is again nominal. Finally, cyber laws and policies of different countries need to be more nuanced such as to allow space for civil liberties. Overall, the propaganda surrounding the malaise of cybercrime seems to be more hype than real. We already have examples of countries who have transgressed into electronic expression in cyber space. Therefore, UN has a valid reason to raise a red flag on this unfolding issue. Originality/value: This paper was published at 21st Americas Conference of Information Systems held at Puerto Rico, USA, between August 13-15, 2015 (AMCIS, 2015). The authors of this paper seek review by Editors of the Journal for Republication of original work. The authors have taken cognizance of the Originality Guidelines for Emerald published at this URLwww.emeraldgrouppublishing.com/authors/writing/originality.htm